Legitimacy, Syncretism, and Bangsamoro Jihad: Discourses of Struggle and Community within the Moro Islamic Liberation Front - Galsim, Miguel (2021)
Islam’s influence in nationalism and political legitimacy is frequently studied, but diversity across the umma warrants continued investigation into how Islamic tradition shapes its style, content, and potency. Investigating the discourse of 1980s Mindanao’s Moro Islamic Liberation Front, this article adopts a syncretic approach for understanding encounters between Islamic traditions, particularly jihad, and nationalist symbols. Through discourse analysis, this article creates a textured understanding of the power of Islamic-nationalism, focusing on both intellectual genealogy and textual practice. It concludes that in this instance, Islamic-nationalism can be an inherently legitimising phenomenon, animated by the uniquely moral, temporal drive of jihadi tradition.
Keywords: Jihad; Legitimacy; Nationalism; Islam; Syncretism; Moro Islamic Liberation Front (MILF)